Affirmative Action Application or Black and White in South Africa Higher Education Institutions: Is it the way forward or not? - Christiena Maria van der Bank; Jafta Mphahlani; Kholeka C Moloi (Intelektual Pustaka Media Utama, 2015)
We will, demonstrate what affirmative action entails, its origin and the relationship with discrimination and equality. The paper will also highlight the implementation of affirmative action in the Higher Education sector in South Africa. Affirmative action or black and white are the additional corrective steps which must be taken in order that those who have been historically disadvantage by unfair discrimination before 1994 are able to derive full benefits from an equitable employment environment. While there has been a significant increase in the number of women appointed into management positions, the proportion in relation to the total number of women in senior posts such as those of Vice Chancellors, Deputy-Vice Chancellors and Executive Deans still remains problematic. Considerations should be taken with regard to issues of access, equity and relevance. Indeed, affirmative action should be located within a rigorous process that will ensure that those who are for example, promoted to senior positions both in private and public sectors are able to demonstrate strategic thinking and action, quality execution of tasks, efficiency and effectiveness in achieving organisational goals. This will also be followed by a brief South Africa’s case study of different entities (South African Breweries and Sowetan Newspaper). A comparison of USA’s affirmative action and whether “there is a light at the end of a tunnel – affirmative action” will be done.